Desenvolvimento de microcápsulas bioativas de coprodutos de suco e vinho da uva visando sua aplicação como antioxidante natural em patê de carne de frango - Pereira, Daiane (2015)
The objective of this study was to evaluate the antioxidant activity of hydroalcoholic extracts and microencapsulated by spray dryer, of different samples of co-products of wine and juice grape varieties Bordô and Niagara (Vitis labrusca) and apply creamy pate of chicken to verify the inhibition lipid oxidation and the acceptance of this product. The grape co-products were extracted individually with ethanol (80%) in shaker at 40 °C / 60 min, concentrated and microencapsulated in spray dryer with maltodextrin 10 DE and capsul®. The dried samples spray dryer were influenced by the encapsulating agent used, where the microencapsulated samples with maltodextrin obtained better efficiency. Microencapsulation of co-products originated smooth beads and other rough, homogeneous in form and structure, without fissures or cracks. The Infrared Fourier Transform analysis (FTIR) showed that the microencapsulated bioactive compounds in the extracts remained even after subjected to drying by spray drying. The hydroalcoholic and microencapsulated extracts showed high phenolic compounds, anthocyanins and flavonoids with antioxidant activity. For the HPLC technique it was possible to identify and quantify six patterns of phenolic compounds (gallic acid, caffeic, coumaric, ferulic, vanillic and trans-resveratrol). The CBGW2 and CBGW2M (MD) extracts were chosen to be applied in creamy pate due to the best levels of phenolic compounds with antioxidant activity. The basic formulation of creamy chicken pate was made with chicken meat, chicken skin and spices and was divided into four treatments: The first was designated as the control and no additional ingredients were included (T1). The second lot was designated as a positive control and was prepared by adding sodium eritorbate (T2). The third lot received liophilized extract CBGW2 (T3). The fourth lot received the CBGW2M (MD) extracts. The stability of chicken meat pates was performed on the day of processing and weekly at 41 days in 4º C by thiobarbituric acid reactive substances index (TBARS) and color. By (ΔE) in color analyses, compared to the control (T1), only the T4 presented visually perceptible influence during the storage period. The pates added 0.3% CBGW2 and CBGW2M (MD) showed satisfactory results for TBARS analysis and were microbiologically according to law. Acceptability levels for the overall evaluation were greater than 70% for T1, T2 and T3 and these extracts of grape wine co-products can be considered an alternative to synthetic antioxidants in pates creamy.